The relationships between interoception and alexithymic trait. The Self-Awareness Questionnaire in healthy subjects - Longarzo, Mariachiara; D'Olimpio, Francesca; Chiavazzo, Angela; Santangelo, Gabriella; Trojano, Luigi; Grossi, Dario (Frontiers in Psychology, 2015)
Interoception is the basic process enabling evaluation of one’s own bodily states. Several previous studies suggested that altered interoception might be related to disorders in the ability to perceive and express emotions, i.e. alexithymia, and to defects in perceiving and describing one’s own health status, i.e. hypochondriasis. The main aim of the present study was to investigate the relationships between alexithymic trait and interoceptive abilities evaluated by the “Self-Awareness Questionnaire” (SAQ), a novel self-report tool for assessing interoceptive awareness. Two hundred and fifty healthy subjects completed the SAQ, the Toronto Alexithymia Scale-20 items (TAS-20), and a questionnaire to assess hypochondriasis, the Illness Attitude Scale (IAS). The SAQ showed a two-factor structure, with good internal consistency (Cronbach’s alpha= .88). We observed significant direct correlations between SAQ, TAS-20 and two of its subscales, and the IAS. Regression analysis confirmed that the difficulty in identifying and expressing emotions is significantly related with awareness for one’s own interoceptive feelings and with a tendency to misinterpret and amplify bodily sensations. From a clinical point of view, the assessment of interoceptive awareness by the SAQ could be pivotal in evaluating several psychopathological conditions, such as the somatoform disorders.